A Gauss-Kuzmin-Lévy theorem for a certain continued fraction - Hei-Chi Chan (International Journal of Mathematics and Mathematical Sciences)
We consider an interval map which is a generalization of the well-known Gauss transformation. In particular, we prove a result concerning the asymptotic behavior of the distribution functions of this map.